METHODS OF SYSTEMIC APPLIED GEOMETRY IN MODELING OF ENERGY EFFICIENT ARCHITECTURAL CONSTRUCTION CLUSTERS: Array - Mykytas, M. (Municipal economy of cities (Technical science), 2019)
When designing cluster sociotechnical systems, there is a large number of tasks that require the synthesis of models of cluster structures, and modeling of patterns that reflect the processes of their functioning and transformation. A separate category of cluster sociotechnical systems consists of adaptive clusters that are defined as cluster entities whose structure and functions are consistent and varied in time with predicted development and change of tasks for which the cluster was formed. Architectural-building clusters are large in terms of the number of elements and complicated by the nature of the system links. Conducting real experiments with such objects is economically inappropriate and limited to problems associated with the uniqueness of each cluster. The main purpose of the work is to highlight the role of system geometric modeling in the design of energy-efficient adaptive architectural and construction cluster sociotechnical systems with pre-set characteristics. The paper shows that system geometric modeling is a powerful tool for studying objects, processes and systems of different nature. The effectiveness of applying the concept of system geometric modeling to a defined class of tasks is as follows. First, this concept operates with all the arsenal of geometric and graphical modeling tools that make up the system hierarchy and have very clear recommendations for the effectiveness of use. Secondly, the technological platform of system geometric modeling is the technology of "counter flows", which compares the structures of the system of the object being modeled, and a certain modeling method from a set of possible systems with the necessary features. The latter determines the reasonableness of the choice of the method from the possible alternatives. Thirdly, the methods of geometric modeling are successfully used in solving the problems of econometrics close to the essence, in particular, the problems of modeling the flow distribution of resources in complex socio-technical systems. Knowledge of system and constructive and operational properties of geometric modeling methods is the basis for performing the search for optimal methods and parameters that best meet the requirements of a particular task. In this case, such a practical task is the synthesis of models of energy-efficient architectural and construction clusters and their components. To solve this problem, a general scheme of coordination of the structure of the object system and the structure of the simulation method is proposed, and the use of the technology of "counter flows" is substantiated. The description of the system of the object, its representations and interpretations at the level of the cluster as a whole and description of the system of the object, its representations and interpretations of cluster structures at the elemental level are given.